A Morphological Study of Some Silene L. Species of Caryophyllaceae family in Iraq - Al-Hadeethi, Muazaz Azeez Hasan; Aljaf, Mouhannad Mahmood; Sutthisaksopo, Phanom (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The current works included morphological features study (vegetative and floral parts) for five species of the genus Silene L., S. ampullata, S. chlorifolia, S. colorata, S. conoidea and S. longipetala belong to the family Caryophyllaceae, samples were collected from various areas of northern Iraq. Confirmation in the description was on the most critical parts of the plant, including the shape of the leaves, length, and shape of the calyx tube and venation, the modification shapes of coronal scales petals and appendages, anther ornamentation and structures of pistils. Images enhanced the morphological characteristics under study. Information on the locations and dates of the collection was also confirmed.